Evaluation of the value of preoperative CYFRA21-1 in the diagnosis and prognosis of epithelial ovarian cancer in conjunction with CA125 - Chunjing Jin; Minfeng Yang; Xueqiao Han; Haidan Chu; Yan Zhang; Meihong Lu; Zhonghui Wang; Xinxin Xu; Wenwen Liu; Feng Wang; Shaoqing Ju (BMC, 2019)
Abstract Growing evidence indicates that the tumor biomarker cytokeratin 19 fragment (CYFRA21-1) is significant for a variety of cancers. However, its role in epithelial ovarian cancer (EOC) has rarely been reported. In this study, a receiver operating characteristic (ROC) curve was utilized to estimate the diagnostic efficiency of CYFRA21-1. The correlation between the CYFRA21-1 level and prognosis was analyzed by Kaplan-Meier survival analysis and univariable and multivariable analyses. The relationship between serum CYFRA21-1 levels and different clinicopathological variables was also analyzed. At the same time, the standard serum marker cancer antigen 125 (CA125) was measured. The results demonstrated that CYFRA21-1 expression was significantly increased in EOC compared with expression in benign ovarian diseases and healthy controls, which was similar to CA125 (P < 0.001). CYFRA21-1 expression was positively correlated with CA125 (r = 0.201; P = 0.0032). CYFRA21-1 expression was significantly correlated with lymph node metastasis and ascites (P < 0.001). Furthermore, the median survival time of EOC patients with high CYFRA21-1 expression was 42 months, compared with 54 months in the low CYFRA21-1 expression patients by Kaplan-Meier analysis (P < 0.05), while the high and low CA125 expression groups had no difference in median survival time. Univariate and multivariate analyses indicated that CYFRA21-1 was a poor prognostic factor associated with overall survival (OS), while CA125 was not. Our study indicates that CYFRA21-1 acts as a good complementary diagnostic biomarker and may be superior to CA125 as a prognostic indicator in EOC.